Elongated uvula: diagnosis and management of a rare condition: case report - N., Harshitha (International Journal of Research in Medical Sciences, 2024)
Elongated uvula is a rare condition where the uvula extends into the oropharynx, causing discomfort such as throat irritation, choking during swallowing, and nocturnal dyspnea. This case study discusses a male patient in his 50s presenting with these symptoms, aiming to highlight the diagnostic process and treatment outcomes. The patient presented with throat irritation, choking sensation while swallowing, and nocturnal dyspnea. Clinical examination by a primary care physician revealed an elongated uvula, which was confirmed through CT imaging. Routine investigations, including CT-PNS scanning and polysomnography (PSG), were conducted. The patient underwent a uvulectomy under local anesthesia in an outpatient setting. Postoperative follow-up assessments were conducted to monitor symptom relief and any complications. CT imaging confirmed the diagnosis of an elongated uvula measuring 54 mm. PSG indicated fragmented sleep architecture. The uvulectomy procedure was performed successfully without complications. The patient reported significant relief from throat irritation and improved swallowing function postoperatively. Follow-up at 1 month showed sustained improvement in symptoms. This case highlights the importance of considering uvulectomy for patients with symptomatic elongated uvula. Accurate diagnosis is essential to differentiate it from other conditions like asthma. Uvulectomy is an effective treatment that can significantly improve symptoms and quality of life for appropriately selected patients. Proper patient selection and preoperative evaluation are crucial for achieving optimal outcomes.